2008
DOI: 10.3174/ajnr.a1019
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Posterior Communicating Artery Aneurysm-Induced Oculomotor Palsy after Coiling

Abstract: BACKGROUND AND PURPOSE:Recovery of oculomotor (cranial nerve [CN] III) palsy after surgery of posterior communicating artery (PcomA) aneurysms has been well documented, but recovery after coiling is poorly understood. In this study, we report the recovery after coiling of PcomA aneurysminduced CN III palsy in 21 patients at follow-up of 1 to 7 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
62
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 15 publications
10
62
1
Order By: Relevance
“…Therefore, overall improvement (partial or complete) occurs in up to 90% of patients undergoing endovascular therapy. These important findings are in agreement with the findings of Hanse et al, 11 who assessed the recovery of ONP with endovascular therapy in 21 patients. The authors found that ONP recovered completely in 38.1% (8/21) of patients and partially in 52.4% (11/21) after endovascular therapy.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Therefore, overall improvement (partial or complete) occurs in up to 90% of patients undergoing endovascular therapy. These important findings are in agreement with the findings of Hanse et al, 11 who assessed the recovery of ONP with endovascular therapy in 21 patients. The authors found that ONP recovered completely in 38.1% (8/21) of patients and partially in 52.4% (11/21) after endovascular therapy.…”
Section: Discussionsupporting
confidence: 82%
“…On the basis of these findings, it is possible that a significant number of patients with partial ONP recovery at their latest follow-up would eventually progress to complete recovery. Our findings contradict those of Chen et al 4 and Hanse et al, 11 who respectively reported that ONP recovery occurs invariably within 6 and 12 months following treatment. This question, however, requires further investigation ideally through large prospective studies with long periods of clinical follow-up.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…20,21 In comparing ours to previous studies regarding clinical follow-up and neurologic outcome of patients presenting with neurologic symptoms from all types of endovascularly treated aneurysms, we found no apparent worse outcome of the endovascularly treated partially thrombosed aneurysms in our study. 2,6,8,10,15,[22][23][24] Partially thrombosed aneurysms might have a different pathogenesis and, therefore, may form a different disease than aneurysms without intraluminal thrombus. Some propose that the vasa vasorum of the aneurysmal wall play a crucial role in the development and growth of aneurysms with intraluminal thrombus by proliferation, inflammation, and rupture.…”
Section: Discussionmentioning
confidence: 99%